1996
DOI: 10.1111/j.1365-2222.1996.tb00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of mast cells, eosinophils and IL‐5 in the development of airway hyperresponsiveness in sensitized mice

Abstract: These data suggest that mast cells play an important role in the onset of airway hyperreactivity but do not play a role in the production of IL-5 and eosinophilia. Furthermore, indicate that the inhibition of IL-5 is not always associated with a reduction in antigen-induced airway hyperreactivity in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Indeed, there are studies supporting the role of mast cells in these models (10,11). However, there are other reports in the literature that question mast cell participation in this response (12)(13)(14)(15). Recently, strong evidence has been presented that ties the role of mast cells in murine models of asthma to the experimental protocols used.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, there are studies supporting the role of mast cells in these models (10,11). However, there are other reports in the literature that question mast cell participation in this response (12)(13)(14)(15). Recently, strong evidence has been presented that ties the role of mast cells in murine models of asthma to the experimental protocols used.…”
Section: Discussionmentioning
confidence: 98%
“…Presently, the participation of eosinophils in the development of AHR is not clear. Studies by Nagai et al (14) and Corry et al (43) showed that the anti-IL-5 Ab treatment inhibited airway eosinophilia, but not AHR. Kobayashi Wild-type and Fc⑀RI␣ Ϫ/Ϫ mice were sensitized to OVA in alum on days 1 and 14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When studying mechanisms of allergic airway disease in animal models, mast cell-deficient mice have variable decreases in eosinophil numbers (31,32) following allergen challenge, but systemically sensitized and challenged mast cell-deficient mice are capable of developing a Th2 response, airway inflammation, and AHR similar to WT control mice (33)(34)(35)(36). In most of these studies, allergen sensitization was achieved by systemically injecting the allergen in combination with an adjuvant, while other studies, using less potent sensitization protocols, demonstrated a more obvious role for mast cells in the development of AHR (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of mast cells in the development of AHR is somewhat controversial. When studying mechanisms of allergic airway disease in animals models, mast cell-deficient mice have variable decreases in eosinophil numbers (10,11) after allergen challenge, but systemically sensitized and challenged mast cell-deficient mice are capable of developing a Th2 response, airway inflammation, and AHR similar to wild-type control mice (12)(13)(14)(15). In most of these studies allergen sensitization was achieved by systemically injecting the allergen in combination with an adjuvant, whereas other studies, using less potent sensitization protocols, demonstrated a more obvious role for mast cells in the development of AHR (16,17).…”
mentioning
confidence: 99%